(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The Caliph Abu Jaafar Al-Mansur (138-158AH/754-775AD) Is considered one of the most important caliphs of the Abbasid state, which lasted for several centuries (132-656AH/750-1258AD), where his rule constituted the golden age of the Abbasid state. He is credited with establishing the pillars of the state, through the political, military, economic, social and urban achievement, he set the Abbasid state on the path of development. The establishment of Baghdad city and making it the capital had a role in making it a destination for scholars and thinkers, who came to it from all parts of the vast country, and this contributed to the progress and development of science, and thus arose the need to benefit from the sciences of previous civilizations (such as the Greek, Byzantine and Persian). The Caliph Al-Mansurs interest with the translation movement, which he singled out for a number of Arab, Byzantine, and Greek scholars, and gave them a lot of money and gifts to achieve his goal, his rule witnessed the translation of a large number of scientific booksin to the Arabic language, which enriched the Arab culture andthought. Keywords: (